Detection and visualization of power system disturbances using principal component analysis - Barocio,E; Pal,BC; Fabozzi,D; Thornhill,NF (2013)
In this paper, a multivariate statistical projection method based on Principal Component Analysis (PCA) is proposed for detecting and extracting unusual or anomalous events from wide-area monitoring data. The method combines PCA with statistical test to detect and analyze anomalous dynamic events from measured data. Simulations based on a transient stability model of the New England Test System are used to demonstrate the ability of the method to detect and extract system events from wide-area data. © 2013 IEEE.